Period Poverty Among Black, Hispanic and Low-Income Communities in the United States: Challenges and Recommendations - Njoku, Anuli; Alhassan, Mubarak; Tohura, Sharaban; Garcia, Kayla (Hygiene, 2025)
Period poverty refers to the lack of access to or affordability of menstrual hygiene supplies such as sanitary products and the inaccessibility of washing facilities, waste disposal and educational materials. Period poverty can significantly affect menstruating individuals’ physical, mental, and reproductive health and emotional wellbeing; negatively impact educational outcomes; cause financial strain; result in absenteeism from work and school; create barriers to healthcare access; and perpetuate poor health outcomes for generations. Barriers to menstrual equity include lack of access to period support, cost, poor sanitary facilities, lack of education, social and cultural stigma, and legal restrictions. Therefore, it is crucial to actively advocate for initiatives to increase access to menstrual hygiene products, raise public awareness, and educate individuals on safe menstrual practices. Approximately 500 million girls and women worldwide and an estimated 16.9 million people in the United States experience period poverty, with the issue being particularly common among marginalized groups such as Black or Hispanic menstruating individuals and those who are homeless, living in poverty, of low income, or attending college. This article investigates the physical, psychological, educational and social impacts of inequitable access to menstrual products, menstrual education, and sanitation facilities among menstruating individuals who are Black, Hispanic or of low income within the United States. We examine the threat this poses to health equity and propose recommendations to address this pervasive issue.
Keywords: Absenteeism; Equity (law); Health care; Hygiene; Poverty; Public health; Sanitation; Socioeconomic status; dept.pch; environmental sustainability; gender disparities; health equity; menstrual education; menstrual health; menstrual health management; menstrual hygiene products; period poverty; period tax; polycystic ovarian syndrome (PCOS); poverty alleviation; women’s health